2019
DOI: 10.1002/ejsp.2642
|View full text |Cite
|
Sign up to set email alerts
|

Political socialization in kindergartens: Observations of ceremonies of the Israeli Jewish holidays and memorial days

Abstract: This study investigated political socialization in Israeli‐Jewish kindergartens. Specifically, it examined the scope of conflict supporting and peace supporting themes that Jewish‐Israeli kindergarten teachers transmit to children during ceremonies of national events. Sixty‐eight observations in 17 state‐secular and state‐religious kindergartens were conducted during five ceremonies: Passover, Holocaust Day, Memorial Day for Israeli Fallen Soldiers, Independence Day, and Jerusalem Day. The findings reveal that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…One way children learn about the conflict narrative is described in a recent observational study in kindergartens in Israel. In this study, ceremonies of key holidays and memorial days were observed (Nasie & Bar‐Tal, 2020). The findings showed that in these ceremonies, Jewish‐Israeli teachers transmitted major themes of the ethos of conflict to children, and provided clear explicit references to the zero‐sum Jewish narrative.…”
Section: Agents Of Early Ethno‐political Socializationmentioning
confidence: 94%
“…One way children learn about the conflict narrative is described in a recent observational study in kindergartens in Israel. In this study, ceremonies of key holidays and memorial days were observed (Nasie & Bar‐Tal, 2020). The findings showed that in these ceremonies, Jewish‐Israeli teachers transmitted major themes of the ethos of conflict to children, and provided clear explicit references to the zero‐sum Jewish narrative.…”
Section: Agents Of Early Ethno‐political Socializationmentioning
confidence: 94%
“…In research examining Holocaust Remembrance Day ceremonies in Israeli kindergartens, kindergarten teachers were found to transmit messages that justify ingroup goals, including collective victimhood, which is salient during these ceremonies. For example, in one kindergarten, the teacher made a comparison between Jews defending themselves during the Holocaust and Israeli soldiers who fight against “all the Arabs who tried to harm us” (Nasie & Bar-Tal, 2020, p. 694).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scholars hypothesize that the role of parents, among other factors of socialization, is even more important in the context of violent intergroup conflict (Nasie & Bar-Tal, 2020). Evidence shows that parents actively transfer the attitudes and beliefs regarding the intergroup conflict to their offspring (Nasie, Diamond, & Bar-Tal, 2016).…”
Section: Family and Eoc: Intergenerational Transmission Of The Beliefmentioning
confidence: 99%